2010
DOI: 10.1093/eurheartj/ehq060
|View full text |Cite
|
Sign up to set email alerts
|

Transapical aortic valve implantation in 100 consecutive patients: comparison to propensity-matched conventional aortic valve replacement

Abstract: Transapical aortic valve implantation is a safe, minimally invasive, and off-pump technique to treat high-risk patients with aortic stenosis. Results of the initial 100 patients are good and compare favourably to conventional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 1 publication
1
77
0
2
Order By: Relevance
“…The procedural success rate was high. Compared to a control group of patients who underwent conventional AVR (by propensity score analysis), 30-day and one-year survival superior for trans-apical TAVI, but this difference was not significant (97).…”
Section: Discussionmentioning
confidence: 74%
“…The procedural success rate was high. Compared to a control group of patients who underwent conventional AVR (by propensity score analysis), 30-day and one-year survival superior for trans-apical TAVI, but this difference was not significant (97).…”
Section: Discussionmentioning
confidence: 74%
“…A recent systematic review (Figulla et al, 2011) incorporating pooled data from multiple studies reported that mean one-year survival after TAVI was 75.9% (range: 64.1% to 87.0%) (Al-Attar et al, 2009;Grube et al, 2008;Himbert et al, 2009;Kapadia et al, 2009;Otten et al, 2009;Rajani et al, 2010;Rodes-Cabau et al, 2010;Thielmann et al, 2009;Walther et al, 2010;Webb et al, 2009a;Ye et al, 2009). In contrast the mean one-year survival rate for patients treated with medical care alone was 62.4% (range: 40.0% to 84.8%; p < 0.01 vs. TAVI), revealing a 13.5% survival advantage in favor of TAVI at one year.…”
Section: Durability Of Tavimentioning
confidence: 99%
“…Transcatheter aortic valve implantation (T-AVI) was first described by Cribier in 2002 [1] and since then has evolved as a routine procedure for high risk patients with aortic stenosis [2,3]. As of June 2010, 10,000 transfemoral (TF) implants of the CoreValve TM prosthesis (Medtronic Inc., Minneapolis, MN, USA) and approximately a similar number of TF and transapical (TA) implants of the Edwards Sapien TM prosthesis (Edwards Lifesciences Inc., Irvine, CA, USA) ( Fig.…”
Section: Introductionmentioning
confidence: 99%